(untitled) (Journal of the College of Basic Education, 2022)
Rational evidence is the field that the Mu’tazila invoke in general, and Judge Abd al-Jabbar al-Mu’tazili in particular, against their opponents, because of its utmost importance in proving their beliefs based on logical evidence, especially in the issue of the arbitrator and the similar, and its clear impact on the continuation of the fundamentalist struggle between Islamic sects, and try to prove what they believe, and we will try in this research to identify: -